Selection response and genetic parameter estimation for feed intake, gain, and feed conversion - Glaze, J.B. Jr.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Performance records of 1459 Polled Hereford cattle born from 1967 through 1979 were analyzed to estimate genetic parameters and the direct and correlated responses that were due to selection for feed conversion. Heritabilities were .24 for intake, .25 for gain, and .14 for feed conversion. The genetic correlation between average daily gain and feed conversion was -.82; correlation between average daily gain and feed intake was .42. Faster-gaining cattle have greater feed intakes and are more efficient. Feed conversion was improved by direct selection. However, it is more economically feasible for breeders to improve feed conversion by selecting for faster rates of gain, rather than selecting for the trait directly.
Keywords: Beef; Selection; Genetic parameters; Feed intake; Average daily gain; Feed conversion